Modulação da expressão dos genes EF1A e PTI-1 no câncer de próstata - Cordeiro, Elisângela Rosa (2006)
Prostate cancer (PCa) has become a serious problem of public health for men. It is the second most diagnosed cancer, and even with the improvement of the clinical, histopathology and chemical techniques of detection, there is still a high mortality rate in consequence of the delayed or inefficient diagnosis of the illness. Finding more specific markers to increase the possibilities of cure and detection of the illness has been the objective of numerous researches. Several components involved on the protein synthesis in eukaryotes have been related with the oncogenic transformation. The alteration on the mRNA levels of the elongation factor 1 (EF1A) expression has been related to different types of cancer. A mutated form of this gene, PTI-1, has been associated with prostate cancer. This gene has an exclusive region of homology to Mycoplasma hyopneumoniae, 5´UTR, and a region of fusion, which contains sequences of homology to the M. hyopneumoniae and to the EF1A. It was originally described in the cellular lineage LNCaP, and its expression has been detected in tumoral cells while corresponding normal cells were negative. Our goal was to analyze the behavior of the expression of those two genes in samples of blood and of patients with PCa, benign prostatic hiperplasia (BPH) and in blood of young healthy men (control). We observed that the expression of EF1A in blood as in tissue was higher in patients of the PCa group. The groups had been subdivided in expression intervals 0.5, 0.5 1.0, 1.0 1.5 and >1.5 for better characterization. The relative levels of expression of the EF1A in tissue were estatistically correlated with the TNM staging, and presented a risk 4.6 times higher of PCa occurrence. In the BPH group, 90% of the patients presented lower mRNA expression levels. In the peripheral blood, we have observed for the interval lower than 0.5 that the probability of being PCa is 3 times higher than in the 1.5 interval, with a risk 10.56 times higher. The 5 UTR and the fusion regions, although observed in high rates in the PCa group, it has also been observed in BPH and the control groups. Its presence associated with EF1A expression level leads us to hipothetize that this gene modulates the EF1A expression in initial and final periods of the illness, determining an increase of the EF1A levels in order to guarantee the cellular proliferation and advance of the tumor confined to the organ; when the passage to metastasis phase occurs, PTI-1 seems to exert a control on the levels of EF1A as to reduce them, thus preventing the cells in the circulation come to suffer apoptosis.